Novel 11-norbetaenone isolated from an entomopathogenic fungus Lecanicillium antillanum. Issue 9 (1st May 2017) - Li, Chi-Ying; Lo, I-Wen; Wang, Shih-Wei; Hwang, Tsong-Long; Chung, Yu-Ming; Cheng, Yuan-Bin; Tseng, Sung-Pin; Liu, Yi-Hung; Hsu, Yu-Ming; Chen, Shu-Rong; Hu, Hao-Chun; Chang, Fang-Rong; et al.
Graphical abstract: Abstract: A novel nor-betaenone compound, 11-norbetaenone (1 ), was isolated from the culture broth of an entomopathogenic fungus Lecanicillium antillanum . The structure was determined on the basis of 1D and 2D NMR spectroscopic data. The absolute stereochemistry of1 was further confirmed by X-ray single crystallography analysis. It is the first secondary metabolite reported from the species Lecanicillium antillanum . And it is also the first time that a betaenone-type compound was isolated from the genus Lecanicillium . Furthermore, 11-norbetaenone (1 ) displayed significant anti-angiogenic effect by suppressing tube formation.